Analisis Karakter Peduli Lingkungan pada Santri dalam Mewujudkan Pesantren Sehat - Almuhaimin, Almuhaimin; Usmaningrum, Desif Upix; Sofiyetti, Sofiyetti (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Background: The concept of disease is the impact of an imbalance between host, agent (disease) and environment. Instilling a culture and character that cares about the environment needs to be done from an early age. Islamic boarding school education is considered to be in line with and able to describe complex forms of society in a simple scope, one of which is Islamic boarding school as an educational institution which is a complex environment for community gathering. This research aims to analyze the relationship between the environmentally caring character that is formed in students and the Clean and Healthy Living Behavior (PHBS) that they follow. Method: This research method is a descriptive observational cross sectional study, namely a research design where measurements and observations are carried out simultaneously at one time. The research subjects were high school students in Jambi City, where the research population was middle school students in Jambi City Islamic boarding schools. The research sample consisted of 111 respondents. Results There is a relationship between the characteristics of caring for the environment and clean and healthy living behavior among Islamic boarding school students. Bivariate analysis using the chi square test showed a p value of 0.002 (<0.05). Conclusion: The character of caring for the environment in students is related to clean and healthy living behavior.